Experts Review on Factors to Consider When Designing Virtual Environment for Stress Therapy - et.al, Farhah Amaliya Zaharuddin (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Virtual reality (VR) based therapy is an alternative technique available for stress treatment. In this technique, virtual reality is used as a tool to assist users to reduce stress and induce relaxation. Many previous literatures published have acknowledged the effectiveness of virtual reality based therapy as compared to other techniques such as breathing exercise and imagination. However, previous studies available only focused on proving the effectiveness of virtual reality application in reducing stress, but are lacking discussions on factors that should be taken into consideration when designing its virtual environment. In previous study, initial framework containing possible factors to be considered when designing virtual environment for stress therapy has been proposed. In this paper, an expert review was conducted to validate the usefulness of the identified factors. Findings from the validation process has resulted in the improved version of the initial framework and their application in virtual environment.